Effect of two boron compounds on smoke‐suppression and flame‐retardant properties for rigid polyurethane foams. Issue 10 (29th April 2022) - Xu, Bo; Zhao, Siheng; Shan, Hao; Qian, Lijun; Wang, Jingyu; Xin, Fei
Abstract: The aim of this work was to improve the smoke‐suppression performance and flame‐retardant effect of a phosphorus‐based bifunctional flame retardant (PDEP)/expandable graphite (EG) binary flame‐retardant system by incorporating two boron‐containing inorganic compounds, zinc borate and boron phosphate (BP), into rigid polyurethane foams (RPUFs). The results revealed that both the boron‐containing inorganic compounds inhibited smoke/heat release of retardant RPUF by accelerating the crosslinking and char forming of the material to promote phosphorus retention in the solid phase. In particular, when 2% BP replaced the same amount of PDEP, the total smoke release value of the RPUF/2%BP/10%PDEP/8%EG (2B10P8E) sample decreased by 30.0% compared with the RPUF/12%PDEP/8%EG (12P8E) sample. This lifted smoke‐suppressive performance mainly due to the existence of Brønsted and Lewis acid sites on BP, which can accelerate the dehydration and crosslinking of hydroxyl in compounds, thus resulting in more phosphorus‐oxygen components retained in the condensed phase, effectively inhibiting the smoke/heat release of the composites. The addition of BP balanced the bi‐phase flame‐retardant effects of RPUF systems containing phosphorus‐based flame retardant due to a strong catalytically charring effect. Thus, the flame‐retardant efficiency was also greatly improved. The smoke‐suppressive and flame‐retardant modes of action of the ternary system was evaluated by experiments using TGA Fourier transform infrared spectroscopy, SEM, energy dispersive spectrometry, pyrolysis‐gas chromatography/mass spectrometry and Fourier transform infrared spectroscopy. © 2022 Society of Industrial Chemistry. Abstract : Smoke suppression mechanism of BP and ZB.